The Role of Supply Chain Management in Competitiveness of Information and Communication Technologies - Perskaya V.V.; Krasavina L.N. (International Journal of Supply Chain Management, 2019)
The article analyzes the state of international and domestic competitiveness of US companies in the field of information and communication technologies, focuses on key segments of the US national competitiveness in ICT based on the supply chain management (SCM); the issues of confrontation with the companies of China and Japan in this field are considered; the issues related to the support of the national competitiveness of the USA by the government on the federal and local levels to enhance the national competitiveness of the United States as a sphere that is also related to ensuring national security of the country in the current conditions of forming a polycentric configuration of the world community are analyzed.